La dimension culturelle dans l’enseignement/apprentissage Du FLE en Algérieanalyse de manuel de 3ème année secondaire. - Larbi TAIF (My University, 2022)
Abstract The cultural dimension in the teaching/learning of French as a foreign language depends, in many cases, on the cultural skills of the teachers. Thus, the teaching of foreign languages aims to exploit the capacities and knowledge of learners to discover the universe, and to know foreign cultures by learning these languages. From this postulate, we carried out an analysis of the third year secondary textbook, it is a survey carried out among third year secondary students of the Ahmed LOULOU high school in the wilaya of Souk-Ahras, a practical experience, which translates into an analytical study of some texts from the textbook and an observation of the progress of the teacher/learner course sessions, in class, with the aim of verifying whether the textbook promotes the learning of a foreign culture, and allows the development of intercultural competence in the target audience ------------------------- Résumé La dimension culturelle dans l’enseignement/ apprentissage du FLE dépend, dans bien des cas, des compétences culturelles des enseignants. Ainsi, l’enseignement des langues étrangères vise à exploiter les capacités et les connaissances des apprenants à découvrir l’univers, et à connaître les cultures étrangères par l’apprentissage de ces langues. A partir de ce postulat, nous avons effectué une analyse de manuel de troisième année secondaire , il s’agir d’une enquête réalisée auprès des élèves de troisième année secondaire du lycée Ahmed LOULOU de la wilaya de Souk-Ahras, une expérience pratique, qui se traduit en une étude analytique de quelques textes du manuel et une observation du déroulement des séances de cours enseignants/apprenants, en classe, dans le but de vérifier si le manuel scolaire favorise l’apprentissage d’une culture étrangère , et permet le développement de la compétence interculturelle chez le public cible .